An underutilised fruit of mangifera pajang kostermans increases antioxidant status in plasma of normocholesterolemic subjects - Ibrahim, Muhammad; Ismail , Amin; Azlan, Azrina; Abd-Hamid, Azizah (Karger, 2013)
Bambangan (Mangifera pajang)is a type of wild mango from family of Anacardiaceae, an under-utilised fruit that can be found in their native area such as East Kalimantan (Indonesia) and Borneo Island (Malaysia-Sabah and Sarawak; Brunei). The fruit is three times larger than commercial mango (Mangifera indica). The fruit is edible and onstitutes one of the common dishes within the local community. The aim of this study was to determine the effect of bambangan juice powder (BJP) drink on plasma vitamins, antioxidant enzymes and together with the liver and kidney function tests.